2016
DOI: 10.1109/jsen.2016.2519531
|View full text |Cite
|
Sign up to set email alerts
|

High Intrinsic Sensitivity Etched Polymer Fiber Bragg Grating Pair for Simultaneous Strain and Temperature Measurements

Abstract: , "High intrinsic sensitivity etched polymer fiber Bragg grating pair for simultaneous strain and temperature measurements," IEEE Sensors Journal, vol. 16, (8) pp. 2453-2459, 2016 High intrinsic sensitivity etched polymer fiber Bragg grating pair for simultaneous strain and temperature measurements Abstract A sensing configuration for simultaneous measurement of strain and temperature with enhanced intrinsic sensitivity based on a fiber Bragg grating (FBG) pair with one grating inscribed in the etched and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 22 publications
(22 reference statements)
0
24
0
Order By: Relevance
“…On the other hand, the FBG filter in a ring laser cavity configuration achieved a resolution of 700 nε and a sensitivity of 74.5 pm/με. The sensor configuration of Reference [ 54 ] is based on a FBG pair (with different Bragg wavelengths): one of them is etched while the other shows an un-etched region of polymer fibre (POF). The strain has been applied by using a translation stage in order to measure the sensitivity.…”
Section: Performance Evaluation Of the Strain Sensorsmentioning
confidence: 99%
“…On the other hand, the FBG filter in a ring laser cavity configuration achieved a resolution of 700 nε and a sensitivity of 74.5 pm/με. The sensor configuration of Reference [ 54 ] is based on a FBG pair (with different Bragg wavelengths): one of them is etched while the other shows an un-etched region of polymer fibre (POF). The strain has been applied by using a translation stage in order to measure the sensitivity.…”
Section: Performance Evaluation Of the Strain Sensorsmentioning
confidence: 99%
“…A Youngs modulus reduction has been reported when a PMMA optical fiber was chemically etched with acetone [17]. The authors claimed that one possible reason for the material property changes could be the molecular chain relaxation due to solvent absorption.…”
Section: Chemical Etchingmentioning
confidence: 99%
“…This is because the distance between the fiber surface exposed to the external environment and the fiber core is less, which can reduce the time that water requires to reach the Bragg gratings location and be detected. However, recently it was shown that etching PMMA with acetone can change not only the physical dimensions of the POF, but also its material properties, such as its Youngs modulus [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, since the first polymer FBG reported in 1999 [22], several promising devices, mainly for the measurement of strain and temperature using step-index fiber and micro-structured fiber have been demonstrated [23][24][25]. Despite of this, for the inscription of the grating, the photosensitivity of the material is important; so far great advances have been done both in doped [26][27][28] and undoped fibers [29], but grating time stability is still an issue if the FBG is not properly annealed [24,30].…”
Section: Introductionmentioning
confidence: 99%